AN ANALYSIS OF ARGUMENT STRUCTURE IN LANGUAGE TEACHING RESEARCH ARTICLE ON DISCUSSION PART PUBLISHED IN IJAL JOURNAL BASED ON TOULMIN ARGUMENT PATTERN ( TAP ) - Annisa Sofia Zikrillah; Ririn Putri Ananda (Teaching English and Language Learning English Journal, 2024)
Writing argumentative is an important skill for anyone in Education world, especially for anyone want to study further in English. In this case this related to every institution will usually publish nationally indexed journals as their benchmark in finding references, one of which is a research sample. The writing in this discussion is choosing objects related to "IJAL (International Journal of Applied Linguistics). The aim is to increase the competitiveness of the publication of Indonesian higher education scientific papers which are still low and far behind compared to countries in the Asian region. International journal publications can increase the visibility of student research at the global level. This research instrument will use an observation checklist, which is a list of things that observers will be see when observing research subjects. This obtain data and lists that would be prepared by the researcher to analyze the component of argument structure. The Researcher found that the elements of argument structure that used in the IJAL journal Sinta 1 from the experts For the first purpose of this research, the data were taken based on argument components contained in the argumentation paragraph of research article then classified the patterns formed from the component based on the completeness of the components the patterns namely, Incomplete, Semi Complete, Almost complete and Complete pattern. Keyterms : Argument Structure, writing an argument, Toulmin Argument Pattern, IJAL journal